No such thing as waste in primary food sector - Kenk, Kadi (Waste management & research : the journal of the International Solid Wastes and Public Cleansing Association, ISWA, 2024)
The European Union (EU) circular economy action plan aims to double its use of recycled material by 2030. We argue that waste-centric approach to resources may have adverse consequences to this ambition. The aim of the work was to find out the factors limiting or promoting the use of waste from primary food sector in countries with the same cultural background and similar climate in Estonia, Latvia, Lithuania and Norway. Biomass from the primary food production sector is of good quality and excellent to use, but its use may be limited if given waste status. From numerous management decision trigger clusters, which may affect valorisation of the biomass, we focus on technology and policy. Our semi-structured interviews addressed the analysis and management of waste or by-products and explored the end-of-waste and alternative mechanisms that allowed the biomass to be valorised. However, the interviews revealed that none of the companies regard anything becoming waste, but as raw material or production left-over. Any obstacles hypothesised turned out not to be acknowledged by companies at all. This appears to be a very good example of the use of resources, but the approach is haphazard and may conflict with official understanding and waste reporting requirements. Definition of waste is the same in the EU, and arbitrary treatment can be misleading. There is a need for better management of the material flow to ensure effective biomass circulation avoiding its becoming waste. We recommend that this be addressed by introducing environmental, social, governance and a self-control system